Analysis of the Influence of HR Information System Quality, Work Discipline, Training, and Career Development on Performance (A Study of Educators in Jatiroto District) - Akhiryan, Muhammad Tabah; Kusdiyanto, Kusdiyanto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the influence of HR information system quality, work discipline, training, and career development on the performance of educators in the Jatiroto District. The method used is a structural model with independent variables including HR information system quality, work discipline, training, and development, and educator performance as the dependent variable. Model evaluation was conducted through tests of convergent validity, discriminant validity, and composite reliability. The results of the study indicate that work discipline and career development have a positive and significant influence on educator performance, while HR information system quality and training do not have a significant effect. The R-squared value of 0.85 indicates that 85% of the variation in performance can be explained by these four variables. These findings highlight the importance of work discipline and career development in improving educator performance and provide implications for human resource management in the education sector, particularly concerning discipline management and career development.